The story sisters : a novel - Hoffman, Alice (Shaye Areheart Books, 2009)
Elv, Claire, and Meg are the Story Sisters, and each has a fate she must meet alone. One on a country road, one in the streets of Paris, and one in the corridors of her own imagination. At once a coming-of-age tale, a family saga, and a love story of erotic longing.